Dynamic change in Siglec-15 expression in peritumoral macrophages confers an immunosuppressive microenvironment and poor outcome in glioma - Chen, Quan; Chen, Bingkun; Wang, Chunhua; Hu, Li; Wu, Qiongwen; Zhu, Yanyang; Zhang, Qiuyu (Frontiers in Immunology, 2023)
Sialic acid-binding immunoglobulin-like lectin-15 (Siglec-15) was reported to be a novel immune checkpoint molecule comparable to programmed cell death 1 ligand 1 (PD-L1). However, its expression profile and immunosuppressive mechanisms in the glioma tumor microenvironment have not yet been fully explored. Here, we investigated Siglec-15 and PD-L1 expression in tumor tissues from 60 human glioma patients and GL261 tumor models. Next, Siglec-15 knockout macrophages and mice were used to elucidate the immunosuppressive mechanism of Siglec-15 impacting macrophage function. Our results demonstrated that high levels of Siglec-15 in tumor tissues was positively correlated with poor survival in glioma patients. Siglec-15 was predominantly expressed on peritumoral CD68+ tumor-associated macrophages, which accumulated to the highest level in grade II glioma and then declined as grade increased. The Siglec-15 expression pattern was mutually exclusive with that of PD-L1 in glioma tissues, and the number of Siglec-15+PD-L1- samples (n = 45) was greater than the number of Siglec-15-PD-L1+ samples (n = 4). The dynamic change in and tissue localization of Siglec-15 expression were confirmed in GL261 tumor models. Importantly, after Siglec15 gene knockout, macrophages exhibited enhanced capacities for phagocytosis, antigen cross-presentation and initiation of antigen-specific CD8+ T-lymphocyte responses. Collectively, our findings suggested that Siglec-15 could be a valuable prognostic factor and potential target for glioma patients. In addition, our data first identified dynamic changes in Siglec-15 expression and distribution in human glioma tissues, indicating that the timing of Siglec-15 blockade is critical to achieve an effective combination with other immune checkpoint inhibitors in clinical practice.